Finding the Voices of Nineteenth Century Urban Mexico - Warren, Rick (History compass, 2003)
The last two decades have seen a dramatic increase in research that focuses on the transition from colony to nation-state for that part of the Americas that would become Mexico during the first half of the nineteenth century. Central to this enterprise has been the challenge to understand endemic political instability from the outbreak of the War of Independence in 1810 to the rise of the Porfirio Díaz regime in the eighteen-seventies. Factions with competing ideologies (federalists and centralists, republicans and monarchists) intermittently gained a shaky hold over national authority, sometimes through peaceful means, most often by force. This upheaval has affected the way researchers approach the era conceptually and methodologically. Much of the traditional historiography dismissed this ‘age of caudillos’ either as a series of personal confrontations among military chieftains or as pure anarchy roaring through the crumbling floodgates of colonial structures. The major sources for this interpretation of Mexico's nineteenth century were the narrative accounts of contemporary participants and observers, both domestic and foreign. A primary obstacle to revision of this orthodoxy is a result of the very instability that needs explanation, since many of the traditional tools of the historian, even the most basic public records, have disappeared, been damaged beyond repair, or were never generated in the first place. The recent proliferation of excellent publications on the era is a tribute to researchers’ diligence in tracking down material and their creativity in working with what is available. Neglected sources from municipal and regional archives - for example, judicial, electoral, and ecclesiastical records - have been used to great effect. In addition, the application of sophisticated quantitative analysis on the one hand and a turn towards cultural history on the other, have altered our understanding of this era and fomented healthy discussions within the field over the nature of the historical inquiry. The endnotes and bibliography for this essay contain only a brief sample of this scholarship.